The role of Fe dopants in phase stability and electric switching properties of Fe-doped VO2. Issue 16 (December 2016) - Zhang, Ruibo; Jin, Hai-Bo; Guo, Deyu; Zhang, Jiasong; Zhao, Zhengjing; Zhao, Yongjie; Li, Jing-Bo
Abstract: The effect of Fe dopants on the metal-insulator transition of VO2 is investigated by X-ray diffraction, Raman spectroscopy and thermal resistance measurements. The transition temperature is observed to decrease first, reach its minima ( 60 °C) at 1.5 at% Fe and then rise with increasing the doping concentration. The M 2 and T phases are determined to be stabilized by the Fe dopants. The stability regions of polymorphic phases of Fe-doped VO2 are examined by Raman spectroscopy and X-ray diffraction. The solubility of Fe in VO2 is determined to be 4 at%. A phase diagram of Fe-doped VO2 is constructed based on the experimental results. The resistance change of samples with the Fe content less than 1.5 at% remains to be 4 orders of magnitude, demonstrating Fe-doped VO2 a promising electric switching material.